Let $G$ be a group and let $a \in G$. Prove that $\langle a \rangle = \langle a^{-1} \rangle$.

(where $\langle a \rangle = \{\ldots,-2,-1,0,1,2,\ldots\} = \{a^k : k \in \mathbb{Z}\}$)

My attempted work:

If $k=0$, then $a^k = e$ ($e$ being the identity element).

Then $(a^{-1})^k = a^{-1\cdot k}=(a^{k})^{-1}=e^{-1}=e$

Since $a \in G$, by inverse property there exists $a^{-1} \in G$ s.t. $a * a^{-1} = e = a^{-1} * a$. And G can be a subgroup of itself. So I think Lagrange's theorem can be used here, but not too sure about that. I believe that if $a^k = e$ and $(a^{-1})^k = e$, then by Lagrange's theorem, order of $a$ divides order of $a^{-1}$. Does this mean $\langle a \rangle$ divides the order of $\langle a^{-1} \rangle$? Nonetheless, I'm unable to establish the relation $\langle a \rangle = \langle a^{-1} \rangle$.


You cannot argue with order because nothing here need be finite. But: By definition, $\langle a\rangle$ is the smallest subgroup of $G$ that contains $a$. As a subgroup, it also contains $a^{-1}$ and with that also the smallest subgroup containing $a^{-1}$. In other words, $\langle a^{-1}\rangle\le \langle a\rangle$. By the same argument $\langle a\rangle\le \langle a^{-1}\rangle$, hence equality.


$\langle a^{-1} \rangle = \{a^{-k} : k \in \mathbb{Z}\} = \{a^{k} : k \in \mathbb{Z}\} = \langle a^k \rangle$

  • $\begingroup$ If I may ask, how are $a^{-k}$ and $a^{k}$ equal in this context? $\endgroup$
    – Cookie
    Feb 2 '14 at 22:00
  • $\begingroup$ They are not equal, it's just that $\mathbb{Z}$ is read "in the opposite order". $\{-k:k\in\mathbb{Z}\} = \{k:k\in\mathbb{Z}\}$ $\endgroup$
    – Traklon
    Feb 2 '14 at 22:01


$$a^{-1}\in\langle a\rangle\quad\land\quad a\in\langle a^{-1}\rangle$$ and notice that if an element $g$ is in a subgroup $H$ then $\langle g\rangle\subset H$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.